Dampak Perdagangan Internasional terhadap Perekonomian di Indonesia - Rezi Ardiansyah; Fikri Kamilia Ikhwanda; Olivia Efendi; Salwa Najah (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to analyze the impact of international trade on Indonesia's economic growth. By reviewing various relevant literature, this study shows that international trade plays an important role in improving the national economy. This study identifies factors that influence international trade performance, such as trade policies, product quality, and infrastructure. The findings show that Indonesia still faces challenges, including dependence on certain commodities and global price fluctuations, which can affect economic stability. Therefore, this study recommends strategic steps for the government to improve the competitiveness of Indonesian products in the international market, such as infrastructure development, strengthening regulations, and collaboration between the public and private sectors. The results of this study are expected to provide insight for policy makers in formulating more effective strategies to advance international trade and Indonesia's economic growth.